Sejarah Pulau Siantan sebagai Pusat Aktivitas Bajak Laut dan Daerah Pelarian Politik pada Abad 18 M - Dedi Arman (Medan Resource Center, 2022)
This paper discusses the history of Siantan Island (Anambas) in the South China Sea as a center of pirate activity (lanun and political escape areas in the 18th century. The writing uses historical historical research methods and uses library research to extract sources. From the research, it is known that a number of nobles from the Sultanate Siak, the Sultanate of Palembang and the Bugis nobility from Luwu moved to Siantan after losing the power struggle in their native area. In Siantan, the nobles gathered strength by relying on the Orang Laut. The existence of the Orang Laut became the main force to become pirates (lanun), rulers of the sea and carry out piracy in the south China sean and The South China Sea and other areas. The act of piracy ois not only political purposes, but also for economic reasons to seek wealth. Marriage ties are a powerful tool in strengthening relations between the immigrant aristocrats and the Siantan people. The nobles in Siantan then returned to their kingdom and successfully seize power. Raja Alam became the Sultan of Siak, the Five Opu Bugis brothers ruled in the Kingdoms of Johor, Riau and Lingga. Meanwhile, Prince Jayawikrama succeeded in seizing the throne of the Sultan of Palembang with the title Sultan Mahmud Badaruddin I.